Respuesta :

Please help me with the last question just write the equation in vertex form
I’ll mark as brainliest
Ver imagen zanabi3

Answer:

option 4

Step-by-step explanation:

Given

f(x) = x² - 5x - 6

To find the zeros let f(x) = 0 , that is

x² - 5x - 6 = 0

Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (- 5)

The factors are - 6 and+ 1, since

- 6 × 1 = - 6 and - 6 + 1 = - 5 , then

(x - 6)(x + 1) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 1 = 0 ⇒ x = - 1

x - 6 = 0 ⇒ x = 6